Pengaruh Pijat Endorphin dan Hipnoterapi Terhadap Skala Nyeri Pasien Paska Operasi Apendiktomi - Wasita, Rangga; Peristiowati, Yuli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The aim of this study was to analyze the differences in the effectiveness of endorphin massage and hypnotherapy on the pain scale after appendectomy surgery in the Surgical Inpatient Room at R. Syamsudin Hospital, SH Sukabumi City. Quantitative research method with an experimental research design, in the form of a pretest posttest control group design. The analysis in this research uses the dependent T test. The research results showed that there was a change in the pain scale with the difference in the mean of respondents in the hypnotherapy group before and after the hypnotherapy intervention of 3.1 with a P value of 0.000. There was a change in the pain scale with a difference in the mean of respondents in the endorphin massage group before and after of 3.0 with a P value of 0.000. In conclusion, there were changes in the pain scale before and after hypnotherapy and endorphin massage interventions Keywords: Hypnotherapy, Endorphin Massage, Pain Scale